Determining the mistakes of secondary school mathematics teachers in operation priority - Tutak, Tayfun; Süzen, Ahmet Burak; İnan, İbrahim Enam (Ozgen Korkmaz, 2020)
The aim of this study is to determine the mistakes made by secondary school mathematics teachers in the operation priority (Order-of-Operations) and to offer solutions to these problems. The research, which is conducted during 2018-2019 academic year in the central district of Elazığ and is limited to fifteen mathematics teachers who had different professional experiences and differed in the departments they graduated from. A form which prepared by experts of the field and consisting of 5 open-ended questions was given to the teachers to get their views on the order of operations. Interview technique was used to determine the knowledge levels of teachers in this qualitative study. Semi-structured interview form was used as data collection tool. Qualitative research method was preferred for collecting, analyzing and interpreting the data of this research. Data analysis and interpretation were based on content analysis method which is among the methods of qualitative research designs. The results are presented in a descriptive manner. According to the results of the research, it is revealed that teachers do not fully know the operation priority rule. Based on the findings and results of the current research, some pedagogical and theoretical implications are presented with a view to enlightening the practitioners and researchers. © 2020, Ozgen Korkmaz. All rights reserved.
Keywords: Four operations; Mathematics Teaching; Mistake; Operation priority (Order-of-Operations)